Piotroski's FSCORE: international evidence - Christian Walkshäusl (Journal of Asset Management, 2020)
Almost 20~years after its publication, Piotroski's (J Account Res 38:1–41, 2000) FSCORE, the composite measure of the firm's fundamental strength remains a strong predictor of subsequent stock returns and future profitability in international markets over the 2000–2018 period. Across developed non-US countries as well as emerging countries, high-FSCORE firms significantly outperform low-FSCORE firms by about 10% per year. Furthermore, FSCORE preserves its return-predictive power in all size segments after controlling for established cross-sectional return determinants, such as firm size, book-to-market, momentum, operating profitability, and investment. The findings are consistent with the view that fundamental information is only gradually incorporated into prices by investors.
Keywords: 330; FSCORE; Fundamental analysis; Stock returns; Return predictability; International markets